Father's Role in Improving Early Childhood Leadership Character Education - Usup Usup; Hamid Patilima (Journal of Childhood Development, 2024)
Character is the psychological, moral, or ethical traits that distinguish one person from another. Leadership is the ability to influence people to be willing to follow guidance or obey one's decisions. This study to determine the understanding of the role of fathers about leadership character education for early childhood. Qualitative research researchers use because the object under study takes place in a natural setting and aims to know, understand, and appreciate carefully and in more depth about the role of fathers in improving early childhood leadership character education at RA Nurul Abror Cibinong. This study shows the results that the father becomes a role model and determines the direction and rules of the family to make children grow and develop their character for the better. Future research is expected to find more qualified factors and solutions to guide fathers as role models in the family